Nonchimeric HLA‐Identical Renal Transplant Tolerance: Regulatory Immunophenotypic/Genomic Biomarkers. Issue 1 (30th July 2015) - Leventhal, J. R.; Mathew, J. M.; Salomon, D. R.; Kurian, S. M.; Friedewald, J. J.; Gallon, L.; Konieczna, I.; Tambur, A. R.; Charette, J.; Levitsky, J.; Jie, C.; Kanwar, Y. S.; et al.
Abstract : We previously described early results of a nonchimeric operational tolerance protocol in human leukocyte antigen (HLA)‐identical living donor renal transplants and now update these results. Recipients given alemtuzumab, tacrolimus/MPA with early sirolimus conversion were multiply infused with donor hematopoietic CD34 + stem cells. Immunosuppression was withdrawn by 24 months. Twelve months later, operational tolerance was confirmed by rejection‐free transplant biopsies. Five of the first eight enrollees were initially tolerant 1 year off immunosuppression. Biopsies of three others after total withdrawal showed Banff 1A acute cellular rejection without renal dysfunction. With longer follow‐up including 5‐year posttransplant biopsies, four of the five tolerant recipients remain without rejection while one developed Banff 1A without renal dysfunction. We now add seven new subjects (two operationally tolerant), and demonstrate time‐dependent increases of circulating CD4 + CD25 +++ CD127 − FOXP3 + Tregs versus losses of Tregs in nontolerant subjects (p < 0.001). Gene expression signatures, developed using global RNA expression profiling of sequential whole blood and protocol biopsy samples, were highly associative with operational tolerance as early as 1 year posttransplant. The blood signature was validated by an external Immune Tolerance Network data set. Our approach to nonchimeric operational HLA‐identical tolerance reveals association with Treg immunophenotypes and serial gene expression profiles. Abstract : The authors describe a nonchimeric tolerance protocol in HLA‐identical renal transplant recipients given multiple infusions of donor immunoselected hematopoietic CD34 + stem cells in which associative biomarkers include CD4 + CD25 +++ CD127 ‐ FOXP3 + PBMC measurements and a characteristic gene expression profile.